Germinação da semente e morfoanatomia da plântula de Calophyllum brasiliense Cambess. (Clusiaceae) - Jesus, Valquíria Aparecida Mendes de (2010)
Calophyllum brasiliense, stands out for its hardwood, medical characteristics, and is excellent for recovery of degraded areas. In the first chapter, this study was to analyze the influence of the mantle of the seeds in their germination. Three experiments were installed, which are in the laboratory, greenhouse and greenhouse. In each experiment, the percentage, speed and mean germination time in six treatments. The treatments consisted of total removal of the mantle, chemical scarification, mechanical scarification, mechanical scarification and permanence in water for two hours, immersion in hot water, and the witness. The design used in the laboratory and greenhouse was completely randomized, as in the nursery used a randomized block design. Each treatment consisted of four replicates of 25 seeds, and the assessments were made daily for a period of 90 days. The data were subjected to analysis of variance. The means of the treatments were compared by t test (LSD) at 5% probability. In the laboratory, the mechanical scarification treatment followed by 2 h in water showed better results from the assessment of total germination and the IVG. In the greenhouse, the total withdrawal of the mantle showed the best results. In the greenhouse, the best results were found in mechanical scarification treatments followed by 2 h in water and chemical scarification. The variable mean was not significantly different in the three experiments were assessed. In the second chapter aimed to an anatomical description of the seedling and tirodentro. The plant material in the greenhouse was evaluated at different stages of development, and analyzes the fresh and fixed in FAA 50. The anatomical analysis was done by the freehand sections and Microtome, according to standard techniques in plant anatomy. The seedling is cryptocotylar and hypogeal, has cataphylls, and presents eophylls and metaphylls simple venation pinnate craspedodromous simple. The root is polyarch, the hypocotyl is very low, the cotyledons have a reservation and starch crop, the epicotyl is of a stem, and eophylls and metaphyll are dorsiventral. The seedling is part of the type and subtype Horsfieldia.